Costly investment, complementarities and the skill premium - Afonso, Óscar (2011)
We propose a new framework to analyse the relationship between the relative high-skilled labour endowment, the skill premium and economic growth. Building on Acemoglu and Zilibotti (2001), we introduce physical capital; internal costly investment in both capital and R&D; and complementarities between intermediate goods. We only find a positive relationship between the relative labour endowment and both the skill premium and economic growth within determined intervals of relative labour endowment values, which vary with the absolute productive advantage of high over low-skilled labour. The model thus accommodates theoretically mixed empirical results on the relative labour endowment–skill premium relationship. We further find that the impact on both the relative labour endowment and the skill premium of a rise in investment costs or in the complementarities degree depends on: (i) the absolute productivity advantage of high over low-skilled labour; and (ii) the relative labour endowment.